Integrated Evaluation of Age-Related Changes in Structural and Functional Vascular Parameters Used to Assess Arterial Aging, Subclinical Atherosclerosis, and Cardiovascular Risk in Uruguayan Adults: CUiiDARTE Project - Daniel Bia; Yanina Zócalo; Ignacio Farro; Juan Torrado; Federico Farro; Lucía Florio; Alicia Olascoaga; Javier Brum; Walter Alallón; Carlos Negreira; Ricardo Lluberas; Ricardo L. Armentano (International Journal of Hypertension)
This work was carried out in a Uruguayan (South American) population to characterize aging-associated physiological arterial changes. Parameters markers of subclinical atherosclerosis and that associate age-related changes were evaluated in healthy people. A conservative approach was used and people with nonphysiological and pathological conditions were excluded. Then, we excluded subjects with (a) cardiovascular (CV) symptoms, (b) CV disease, (c) diabetes mellitus or renal failure, and (d) traditional CV risk factors (other than age and gender). Subjects (n=388) were submitted to non-invasive vascular studies (gold-standard techniques), to evaluate (1) common (CCA), internal, and external carotid plaque prevalence, (2) CCA intima-media thickness and diameter, (3) CCA stiffness (percentual pulsatility, compliance, distensibility, and stiffness index), (4) aortic stiffness (carotid-femoral pulse wave velocity), and (5) peripheral and central pressure wave-derived parameters. Age groups: ≤20, 21–30, 31–40, 41–50, 51–60, 61–70, and 71–80 years old. Age-related structural and functional vascular parameters profiles were obtained and analyzed considering data from other populations. The work has the strength of being the first, in Latin America, that uses an integrative approach to characterize vascular aging-related changes. Data could be used to define vascular aging and abnormal or disease-related changes.